Revisiting the Intractable Barriers Affecting Medication Adherence Among Outpatients with Schizophrenia - Julaeha, - (The Association of Biotechnology and Pharmacy (ABAP), 2020)
Medication adherence is one of the foremost problems affecting antipsychotic efficacy in schizophrenia patients. Medication nonadherence among schizophrenia patients has been often estimated > 50%, leading to higher rates of relapse and hospitalization as well as to decreasing cognitive and functional prognosis. The purpose of the study is to identify the strategy for improving medication adherence in schizophrenia and evaluate adherence using Medication Adherence Rating Scale (MARS) and determinant factors affecting adherence. Prospective study with cross sectional design was conducted from October to December 2019. Especially data from schizophrenia outpatients in one of national mental hospital in Indonesia. Schizophrenia outpatients were majority male (60%), the age range from 31-49 years were 70%, most of patients are single (63,33%), 70% have secondary education, 70% of them are from Surabaya area, and half of them their duration of the disease from 1 to 5 years. This study showed that the pattern of prescription of antipsychotics are risperidone and clozapine were the most antipsychotics prescribed. 40% of patients have good adherence, 40% of patients have partial adherence, and only 20% of patients' poor adherence. Most of schizophrenia outpatients have experience in forget to take his/her medicine and careless at times about taking his/her medicine and less knowledge about schizophrenia. In other hand, 100% patients have agreed by staying on medication, it can prevent getting sick. The mental hospital should utilize educational program to improve patient's awareness about their disorder and their medications to improve their adherence.